THE ABILITY OF ELEVENTH GRADE STUDENTS WRITING HORTATORY EXPOSITION TEXT AT MAN 1 PEKANBARU - Prasetiani, Deni; Aruan, Rumiri; ', Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to investigate the level of the eleventh grade students’ ability of MAN 1 Pekanbaru in writing hortatory exposition text. The research design is a descriptive quantitative research. There were 32 students chosen as the samples of this research and it was from XI Science 4 class. The instrument of this research was a writing test analyzed by using scoring system adapted from Anderson in Huges (1989) and the students’ scores were matched with ‘The Student Mastery Level’ adapted from Harris (1974). The data show that there were no students who reached excellent level and 1 student (3.13%) was in very good level. Then, there were 13 students (40.63%) who were in good level and 10 students (31.25%) who were in fair level. Moreover, 7 students (21.88%) were in poor level and 1 student (3.13%) was in very poor level. From the collected data, it could be concluded that this eleventh grade students’ ability level of MAN 1 Pekanbaru in writing hortatory exposition text was categorized into fair level. Besides, from the five writing indicators assessed, it was found that the students did the best in vocabulary and style with 3.51 as the average score and the students found it difficult in organization indicator (2.98).Key Words: student, ability, writing, hortatory exposition